@@ -29,19 +29,19 @@ Rebol [
29
29
ref1: yes --assert all [error? e: try [fce/: ref1 "a" ] e/id = 'no-arg]
30
30
ref1: off --assert all [error? e: try [fce/: ref1 "a" ] e/id = 'no-arg]
31
31
ref1: yes --assert all [error? e: try [fce/: ref1 "a" "" ] e/id = 'expect-arg]
32
- ref1: off --assert (fce/: ref1 "a" "" ) == ["a" #[false ] #[none] #[none] #[none] #[none]]
33
- ref1: yes --assert (fce/: ref1 "a" 1 ) == ["a" #[true] 1 #[none] #[none] #[none]]
34
- ref1: off --assert (fce/: ref1 "a" 1 ) == ["a" #[false ] #[none] #[none] #[none] #[none]]
35
- ref1: yes --assert all [(fce/: ref1 "a" x: 1 + 1 ) == ["a" #[true] 2 #[none] #[none] #[none]] x == 2 ]
36
- ref1: off --assert all [(fce/: ref1 "a" x: 1 + 1 ) == ["a" #[false ] #[none] #[none] #[none] #[none]] x == 2 ]
32
+ ref1: off --assert (fce/: ref1 "a" "" ) == ["a" #[none ] #[none] #[none] #[none] #[none]]
33
+ ref1: yes --assert (fce/: ref1 "a" 1 ) == ["a" #[true] 1 #[none] #[none] #[none]]
34
+ ref1: off --assert (fce/: ref1 "a" 1 ) == ["a" #[none ] #[none] #[none] #[none] #[none]]
35
+ ref1: yes --assert all [(fce/: ref1 "a" x: 1 + 1 ) == ["a" #[true] 2 #[none] #[none] #[none]] x == 2 ]
36
+ ref1: off --assert all [(fce/: ref1 "a" x: 1 + 1 ) == ["a" #[none ] #[none] #[none] #[none] #[none]] x == 2 ]
37
37
ref1: yes ref2: yes --assert (fce/:ref1/: ref2 "a" 1 + 1 x y) == ["a" #[true] 2 #[true] x y]
38
38
ref1: yes ref2: yes --assert (fce/:ref2/: ref1 "a" x y 1 + 1 ) == ["a" #[true] 2 #[true] x y]
39
- ref1: yes ref2: off --assert (fce/:ref1/: ref2 "a" 1 + 1 x y) == ["a" #[true] 2 #[false ] #[none] #[none]]
40
- ref1: yes ref2: off --assert (fce/:ref2/: ref1 "a" x y 1 + 1 ) == ["a" #[true] 2 #[false ] #[none] #[none]]
41
- ref1: off ref2: yes --assert (fce/:ref1/: ref2 "a" 1 + 1 x y) == ["a" #[false ] #[none] #[true] x y]
42
- ref1: off ref2: yes --assert (fce/:ref2/: ref1 "a" x y 1 + 1 ) == ["a" #[false ] #[none] #[true] x y]
43
- ref1: off ref2: off --assert (fce/:ref1/: ref2 "a" 1 + 1 x y) == ["a" #[false ] #[none] #[false ] #[none] #[none]]
44
- ref1: off ref2: off --assert (fce/:ref2/: ref1 "a" x y 1 + 1 ) == ["a" #[false ] #[none] #[false ] #[none] #[none]]
39
+ ref1: yes ref2: off --assert (fce/:ref1/: ref2 "a" 1 + 1 x y) == ["a" #[true] 2 #[none ] #[none] #[none]]
40
+ ref1: yes ref2: off --assert (fce/:ref2/: ref1 "a" x y 1 + 1 ) == ["a" #[true] 2 #[none ] #[none] #[none]]
41
+ ref1: off ref2: yes --assert (fce/:ref1/: ref2 "a" 1 + 1 x y) == ["a" #[none ] #[none] #[true] x y]
42
+ ref1: off ref2: yes --assert (fce/:ref2/: ref1 "a" x y 1 + 1 ) == ["a" #[none ] #[none] #[true] x y]
43
+ ref1: off ref2: off --assert (fce/:ref1/: ref2 "a" 1 + 1 x y) == ["a" #[none ] #[none] #[none ] #[none] #[none]]
44
+ ref1: off ref2: off --assert (fce/:ref2/: ref1 "a" x y 1 + 1 ) == ["a" #[none ] #[none] #[none ] #[none] #[none]]
45
45
46
46
===end-group===
47
47
0 commit comments